Minimum Wages and Aggregate Job Growth: Causal Effect or Statistical Artifact? - Arindrajit Dube (Institute for the Study of Labor (IZA), 2013)
A recent paper by Meer and West argues that minimum wages reduce aggregate employment growth, and that this relationship is masked by looking at employment levels. I also find a negative association between minimum wages and aggregate employment growth using both the Business Dynamics Statistics and the Quarterly Census of Employment and Wages datasets, and it is sizable for some time periods. However, I show that this negative association is present in exactly the wrong sectors. It is particularly strong in manufacturing which hires very few minimum wage workers. At the same time, there is no such association in retail, or in accommodation and food services which together hire nearly 2/3 of all minimum wage workers. These results indicate that the negative association between minimum wages and aggregate employment growth does not represent a causal relationship. Rather the association stems from an inability to account for differences between high and low minimum wage states and the timing of minimum wage increases. Consistent with that interpretation, when I use bordering counties to construct more credible control groups, I find no such negative correlation between minimum wages and overall employment growth.
Keywords: J23; J38; 330; minimum wage; employment growth